Uji selektivitas fraksi Rf < 0,5 ekstrak MeOH biji putat air (Barringtonia racemosa) terhadap ikan mujair (Oreochromis mossambicus) - Musri Musman; Sofia S; Adli W Perdana (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The objective of the present study was to evaluate the selectivity of the Rf 0.5 fraction of MeOH extract of putat air kernels (Barringtonia racemosa) on golden snail (Pomacea canaliculata) and tilapia (Oreochromis mossambicus). The research was conducted on November 2011 to February 2012 at Chemical Laboratory of Teacher Training and Education Facultyand Marine Chemical Laboratory of Coordinatorate of Marine and Fisheries of Syiah Kuala University. Thin-layer chromatography was used as the separation technique towards component compounds in the extract samples. The research was used five levels concentration of Rf 0.5 fraction of MeOH solution (20 ppm, 40 ppm, 60 ppm, 80 ppm, 100 ppm) with three repetitions. Mortality rates of golden snails and tilapia were detected when they were exposure to Rf 0.5 fraction of MeOH extract of B. racemosa kernels. The data were analyzed by Probit, and selectivity value (S) was calculated by Feng and Wang formula. The results revealed that Rf 0.5 fraction of MeOH extract of putat air kernels was selective to golden apple snails.Key words. Thin-layer chromatography, mortality, Probit, and moluscida